THE MECHANISM OF LANGUAGE DEATH: A REFLECTION TO OUR LOCAL LANGUAGE - Neng Syifa Masnoneh (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
A lingua franca is important for a multilingual country. For this reason, BahasaIndonesia is designed as a lingua franca for more than 700 local languages in Indonesiato unite people from different social and cultural backgrounds. During colonialism era,Bahasa Indonesia seemed successful in creating a sense of identity as Indonesians.However, the domination of Bahasa Indonesia tends to replace Sundanese, particularlyin children. Sundanese seems poorly transferred to young generation. This paperproposes a research toward the mechanism of language death as a reflection forSundanese language which undergoes shifting; a process that may lead to languagedeath.